Social sustainability of micro, small, and medium enterprises: the case of Makassar city, Indonesia - Ansar, Muhammad Chaeroel; Tsusaka, Takuji W.; Syamsu, Suhardiman (Frontiers in Sustainability, 2025)
The social dimension of sustainability of urban MSMEs (micro, small, and medium enterprises) is understudied compared to the economic and environmental dimensions. This study assesses social sustainability of MSMEs in Makassar city, Indonesia and its relations with economic and environmental sustainability using primary data collected from 300 MSME owners and managers. The empirical analysis employs descriptive statistics and the regression method. Reasonably high levels of social sustainability of MSMEs were found in Makassar, and significant relation with economic and environmental sustainability was identified. In terms of social justice and equity (SJE), more than 80% of the respondents gave positive evaluations toward this dimension, while just under 10% gave negative perceptions. Likewise, the subdimensions of social capital (SCA) and social cohesion (SCO) received mostly positive responses (77 and 86%, respectively). The economic dimension was positively related with SJE and SCA and negatively related with SCO. In contrast, the environmental dimension had a negative relation with SJE and a positive relation with SCA. The findings suggest that devoting greater attention to social sustainability may lead to enhanced economic performance and improved environmental care. The study contributes to evidence of the application of the social principle to economic development and environmental care practices.